Visiting legal systems using S-D logic lens: the impact on operations - Martins, A. (Euroma 2016 - Interactions, 2016)
Service-Dominant logic supports that value is not created by the supplier, that value is co-created. The judicial system is conservative and its output is traditionally seen as the solving of disputes. This paper aims at analyzing the adjustments required in the traditional conceptual logic of legal service systems to perceive it in the lens of service-dominant logic. The European Small Claims Procedure is used as a discussion case. Service-Dominant logic is visited and interpretation in the legal system is attempted. A new conceptualization of the traditional input-process/experience-output perspective in public services, specifically in the legal systems, is provided.